Effect Of Cow Urine Distillate On Carbendazim Induced Toxicity In Albino Rats With Reference To Haemato-Biochemical Profile - Sharma, Sankalp; Jain , N.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The present investigation was undertaken to study the haemato- biochemical alterations caused by administration of carbendazim and to evaluate the ameliorative effect of cow urine distillate in albino rats. The study reveals that the toxic effect of dietary fungicide was suppressed by cow urine distillate significantly.